2013
DOI: 10.1590/s0102-695x2012005000140
|View full text |Cite
|
Sign up to set email alerts
|

Combretum lanceolatum flowers extract shows antidiabetic activity through activation of AMPK by quercetin

Abstract: The present study evaluated the antidiabetic activity of the Combretum lanceolatum Pohl ex Eichler, Combretaceae, flowers extract (ClEtOH) in diabetic rats. Streptozotocin-diabetic rats were divided into four groups: diabetic control, diabetic treated with 500 mg/kg of metformin and diabetic treated with 250 or 500 mg/kg of ClEtOH for 21 days. The treatment of diabetic rats with 500 mg/kg of ClEtOH promoted an increase in the weight of liver, white adipose tissues and skeletal muscles, improving body weight ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
1
22
0
1
Order By: Relevance
“…These results confirm previous findings regarding the antidiabetic activity of ClEtOH (Dechandt et al 2013), allowing the investigation of the hepatic mechanisms of action of the extract.…”
Section: Confirmation Of the Antidiabetic Activity Of Cletohsupporting
confidence: 91%
See 4 more Smart Citations
“…These results confirm previous findings regarding the antidiabetic activity of ClEtOH (Dechandt et al 2013), allowing the investigation of the hepatic mechanisms of action of the extract.…”
Section: Confirmation Of the Antidiabetic Activity Of Cletohsupporting
confidence: 91%
“…Previous studies demonstrated that ClEtOH reduced plasma glucose levels in STZ-diabetic rats after 21 d of treatment; the extract also reduced the urinary urea levels and the mass loss of soleus and EDL skeletal muscles (Dechandt et al 2013), indicating a possible role in the inhibition of gluconeogenesis. Attempting for this, the present study showed that at least part of the antihyperglycaemic effect of ClEtOH is related to the reduction of the hepatic glucose output, since its production was reduced in liver of diabetic rats treated with ClEtOH.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations